Objektifikasi Penafsiran Al-Qur’an sebagai Upaya dalam Menguatkan Wawasan Kebangsaan - Beta Pujangga Mukti (Universitas Ahmad Dahlan, 2022)
The Qur'an, the first maṣdar tasyrī', teaches the importance of building unity. Recent phenomena have actually shown the opposite. Some groups want to build Indonesia only with the spirit of nationality, but other groups want to base it only on religion. Even these two poles of thought are throwing accusations at each other. Indonesia's development cannot be based solely on the spirit of nationality or religion alone. This of course is no longer relevant. This paper examines the above problems with the descriptive-analytical method. The researcher presents the facts of the relationship pattern of religion and nationalism or Islam and nationality (das sein), then the researcher offers the pattern of relationships that should be sought by each element of the nation (das sollen). This study concludes that the pattern of the relationship between religion and nationalism or Islam and nationality needs to be brought from an attitude of subjectivity to an attitude of objectivity. If the aspect of subjectivity comes out, in the sense of believing in each other's truth and accusing the other of being wrong, it can lead to SARA. Therefore, both religion and nationalism or Islam and nationality need to bring up objective values ​​as a common denominator, namely a common reference in building Indonesia. Al-Quran, maṣdar tasyrī‘ pertama, mengajarkan pentingnya membangun persatuan Fenomena yang terjadi akhir-akhir ini justru menunjukkan fakta sebaliknya. Sebagian kelompok ingin membangun Indonesia hanya dengan spirit kebangsaan, namun di kelompok lain ingin mendasarkan hanya pada agama. Bahkan kedua kutub pemikiran ini saling melontarkan tuduhan. Pembangunan Indonesia tidak dapat didasarkan hanya pada spirit kebangsaan atau agama semata. Hal ini tentu sudah tidak lagi relevan. Makalah ini mengkaji problematika di atas dengan metode deskriptif-analisis. Peneliti menyajikan fakta pola hubungan agama dan nasionalisme atau Islam dan kebangsaan (das sein), kemudian peneliti menawarkan pola hubungan yang seharusnya diusahakan oleh setiap elemen bangsa (das sollen). Kajian ini menyimpulkan bahwa pola hubungan agama dan nasionalisme atau Islam dan kebangsaan perlu dibawa dari sikap subjektivitas kepada sikap objektivitas. Jika aspek subjektivitasnya yang keluar, dalam arti meyakini kebenaran masing-masing dan menuduh yang lain salah, maka bisa menimbulkan SARA. Oleh karena itu, baik agama dan nasionalisme atau Islam dan kebangsaan perlu memunculkan nilai objektif sebagai common denominator, yaitu rujukan bersama dalam membangun Indonesia.